Children's Education In The Family In Terms Of Al-Qur'an, Letter Luqman Verse 12-19 Study Of Al-Azhar Interpretation - Ahmat Nuril; Zainuddin Maliki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Abstract:This study aims to find out and describe children's education in the family in terms of al-Qur'an, letter Luqman verse 12-19 study of al-Azhar interpretation. This research is a type of qualitative descriptive research. Data collection techniques in this study use library research methods. While data analysis techniques are used with the tahlili method and content analysis method. The results of the study show that the main points of children's education in the family are contained in the verses of the Luqman verse 12-19 as follows: 1). Aqidah education is the command to purify monotheism to Allah SWT, 2). The worship education is the command to uphold five times prayer in congregation and sunnah prayer, 3). Muamalah education is doing good and preventing evil, 4). Moral education includes; give thanks to Allah SWT, devote to parents, be gentle, be patient, charity sincerely because of Allah SWT, be polite, be a noble character, prohibition to be arrogant, prohibition of pride, be good when walking, prohibition of hardening when speaking, and prohibition on rebuking. Keywords: Child, family education, Q.S. Luqman Verses 12-19, interpretation meaning of al-Azhar